2016
DOI: 10.1016/j.mayocp.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use in Older Adults: Dangers, Management, and Alternative Therapies

Abstract: Several major medical and psychiatric organizations, including the American Geriatrics Society, advise against using benzodiazepines or nonbenzodiazepine hypnotics in older adults. Despite these recommendations, benzodiazepines continue to be massively prescribed to a group with the highest risk of serious adverse effects from these medications. This article summarizes legitimate reasons for prescribing benzodiazepines in the elderly, serious associated risks of prescribing them, particularly when not indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 23 publications
6
110
0
6
Order By: Relevance
“…31 Thus, use of anticholinergic drugs should generally be avoided among people with dementia. 32 A systematic review looking at the use of benzodiazepines in people with AD found a high prevalence of benzodiazepine use, ranging from 8.5% to 20%, 33 which is in line with our findings. 31 In our study, the prescribing of benzodiazepines for periods of 4 weeks or longer was the second most common STOPP criteria, occurring in more than 27% of people dispensed medicines for dementia.…”
Section: Prevalence Of Individual Stopp Criteriasupporting
confidence: 89%
“…31 Thus, use of anticholinergic drugs should generally be avoided among people with dementia. 32 A systematic review looking at the use of benzodiazepines in people with AD found a high prevalence of benzodiazepine use, ranging from 8.5% to 20%, 33 which is in line with our findings. 31 In our study, the prescribing of benzodiazepines for periods of 4 weeks or longer was the second most common STOPP criteria, occurring in more than 27% of people dispensed medicines for dementia.…”
Section: Prevalence Of Individual Stopp Criteriasupporting
confidence: 89%
“…Many were receiving anticholinergic medications or benzodiazepines, recommended to be avoided in patients with delirium and DEM 27,28. This finding is consistent with research in other care settings where delirium symptoms overshadow DEM symptoms when comorbid.…”
supporting
confidence: 77%
“…Therefore, professionals who prescribe this type of medication need to pay attention and carefully evaluate the real need for this therapy, prioritizing pharmacological and non-pharmacological measures that are alternative to their use (41) .…”
Section: Discussionmentioning
confidence: 99%